Smart Monetization: Gen Z Teenagers' Tiktok and Youtube Income Optimization Through Portfolio Theory - Debi Carolina Debi; Muhamad Helmi; Faitullah Faitullah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study analyzes the application of Markowitz Portfolio Theory to the investment management of Gen Z teenagers who earn income from digital platforms such as TikTok and YouTube in Palembang City. Using a quantitative approach with a sample of 300 student respondents as content creators, this study calculates expected return, variance, standard deviation, and covariance to form an optimal portfolio. The results show that the combination of income from TikTok and YouTube with equal weighting produces a portfolio return of 3.36 with lower risk (standard deviation 11.18) than individual assets. This research contributes to digital financial literacy by recommending diversification strategies to manage volatile income. The findings align with the low financial literacy of Indonesian youth (65.43% by 2024) and support the 90% financial inclusion target in South Sumatra.